Central Incisor with Pulp Canal Obliteration and Apical Periodontitis Managed with a 3D Printed-Guided Endodontic Therapy: A Case Report - Abdulaziz Abdulwahed (Journal of Pharmacy and Bioallied Sciences)
This case report discusses a case of a maxillary central incisor with pulp canal obliteration (PCO), managed by guided endodontic access. A preoperative periapical (PA) radiograph and cone beam computed tomography (CBCT) displayed an incidental finding of a periapical radiolucency (PARL), indicating a PA lesion of endodontic origin on tooth #11. An intraoral three-dimensional (3D) scan was obtained, and its data and CBCT images were processed using planning software. A digital model of the guide was designed and 3D printed. The guide was placed on the tooth surface, and the tooth was accessed until the desired length was reached and the canal was located. Non-surgical root canal treatment was conducted, and the canal was obturated with gutta-percha and bioceramic sealer. A final restoration was placed with flowable composite along with the placement of a full ceramic crown. A 1-year recall showed complete healing of the apical area.